Clinic audit for long-term survivors of childhood cancer. Issue 5 (November 1996) - Eiser, C; Levitt, G; Leiper, A; Havermans, T; Donovan, C
Abstract : Follow up for survivors of childhood cancer is considered essential in order to document any continuing impact on growth, fertility and other systems, as well as provide appropriate care and information to individuals themselves. Appropriate follow up needs to take into account the survivors' own views about reasons for attendance and perceived satisfaction with the services provided. Information was sought from 93 survivors (more than five years from diagnosis) and 68 of their parents regarding current attendance, understanding of the purpose of the clinic and satisfaction, and future preferences. Patients' main reasons for attending were to gain reassurance that they were well and information about the disease. There were some discrepancies between the types of information patients would like from clinic attendance and what they remembered being given. Parents were more positive than patients. Our data suggest that (i) knowledge in survivors is poor and (ii) it may be possible to define a subgroup for whom less frequent follow up is appropriate. A key component of care must involve education of patients, both about their past and the implications for future health.